Flexible habitat choice by aphids exposed to multiple cues reflecting present and future benefits. (3rd February 2021) - Yin, Wandong; Xue, Qi; Tian, Baoliang; Yang, Shujian; Li, Zhengying; Chen, Zhaozhao; Ryan, Michael J; Hoffmann, Ary A
Abstract: Mothers choose suitable habitats for laying offspring to maximize fitness. Because habitat quality varies in space and time, mothers gather information to choose among available habitats through multiple cues reflecting different aspects of habitat quality at present and in the future. However, it is unclear how females assess and integrate different cues associated with current rewards and future safety to optimize oviposition/larviposition decisions, especially across small spatial scales. Here, we tested the individual and interactive effects of leaf surface, leaf orientation, and leaf bending direction on larviposition site choice and fitness benefits of wheat aphids ( Metopolophium dirhodum ) within individual leaves. We found that females preferred upper over lower surfaces for gaining current food-related rewards, downward- over upward-facing surfaces for avoiding potential abiotic risks, and sunken over protruding surfaces for avoiding potential biotic risks. When facing conflicting cues during larviposition, females preferred downward-facing/sunken surfaces over upper surfaces, suggesting that females prioritize potential safety at the cost of current rewards during decision making. Most importantly, our combined-cue experiments showed females still assessed secondary cues (i.e., the upper surface) when first-ranked cues (i.e., the downward-facing/sunken surface) are available, even though females only gained relatively small fitness rewards through secondary cues, and females can integrate different cues associated with current rewards and potential safety in a multiplicative way to make flexible and complex larviposition decisions. Overall, our findings provide new insights into how animals collect and process multi-cue information associated with current rewards and potential safety to maximize fitness at small spatial scales. Abstract : Like other animals including human beings, insects often face a dilemma in deciding between small immediate benefits and large potential future benefits. Here, we found that female aphids with simple nervous systems favor potential habitat safety at the cost of gaining small immediate feeding benefits, and also that they integrate cues associated with immediate and potential future benefits in complex ways when making decisions.